A Numerical Study of Complex Reconstruction in Inverse Elastic Scattering. (17th May 2016) - Hu, Guanghui; Li, Jingzhi; Liu, Hongyu; Wang, Qi
Abstract: The purpose of this paper is to numerically realize the inverse scattering scheme proposed in [19] of reconstructing complex elastic objects by a single far-field measurement. The unknown elastic scatterers might consist of both rigid bodies and traction-free cavities with components of multiscale sizes presented simultaneously. We conduct extensive numerical experiments to show the effectiveness and efficiency of the imaging scheme proposed in [19]. Moreover, we develop a two-stage technique, which can significantly speed up the reconstruction to yield a fast imaging scheme.